The Equal Protection Problem in Sexual Harassment Doctrine - Lehman, Brian (Columbia Journal of Gender and Law, 2000)
For twenty years, women have sued their employers under Title VII for sexual harassment perpetrated by men, asserting that the sexual harassment qualified as sex discrimination. In Oncale v. Sundowner Offshore Services Inc., the Supreme Court unanimously held that Title VII also recognizes same- sex sexual harassment. Thus, men may also sue their employers when other men sexually harass them at work. Oncale emphasized that plaintiffs in same-sex sexual harassment cases must satisfy Title VH’s statutory requirements. In pertinent part, Title VII makes it “an unlawful employment practice . . . to discriminate against any individual with respect to his compensation, terms, conditions, or privileges of employment, because of such individual’s … sex.” The Supreme Court stressed that plaintiffs must prove that the harassment happened “because of such individual’s . . . sex” and outlined briefly three evidentiary routes plaintiffs might take to prove this element. The first evidentiary route is sexual desire. In same-sex cases, plaintiffs may satisfy the requirement by proving the harasser is homosexual. Likewise, plaintiffs in male-female cases may rely on the harasser’s heterosexuality. The Court reasoned that in such situations, the combination of sexual proposals and the harasser’s sexual orientation could lead a factf’mder to reasonably assume that the harassment occurred out of sexual desire, and thus “because of sex.” The second evidentiary route is general hostility. Oncale explained this evidentiary route with an example, stating that factf’mders could find discrimination if a female harasses another female in such sex-specific and derogatory terms as to make it apparent that a general hostility toward women motivated the harasser. For this second evidentiary route, factf’mders presumably look at the conduct without regard to the harasser’s sexual orientation. The third evidentiary route is direct evidence showing that the harasser treated men and women differently in a mixed-sex workplace.